Leader Forgiveness and Employee’s Unethical Pro-organizational Behavior: The Roles of Gratitude and Moral Identity - Lu, Lu; Huang, Yuchu; Luo, Jia (Frontiers in Psychology, 2021)
Leader forgiveness refers to the abandonment of anger, resentment, and the desire to revenge against the offender, and it not only means forgiving errors or mistakes made by employees, but also means empathizing and understanding employees, and to see things from another point of view. This research examines the possible “dark side” of leader forgiveness by examining its influence on employee’s unethical pro-organizational behavior, as well as the mediating effect of gratitude and the moderating effect of moral identity. We used questionnaire survey methodology to collect data from 263 Chinese employees to test our hypotheses. Results show that leader forgiveness had a positive influence on employee’s unethical pro-organizational behavior, and gratitude mediated the influence of leader forgiveness on unethical pro-organizational behavior. The relationship between gratitude and unethical pro-organizational behavior, and the indirect influence of leader forgiveness on unethical pro-organizational behavior through gratitude, were moderated by moral identity. Theoretical and practical implications are discussed.